Comportamiento sexual de Alpaida veniliae (Araneae: Araneidae) - Benamú, Marco Antonio (2012)
Studies in transgenic soybean cropsin Buenos Aires province, Argentina, revealed that Alpaida veniliae is one of the most abundant species in the guild of orb web spiders. This species is an effective natural enemy of insect pests affecting this crop. In the present study we carried out a descriptive and quantitative analysis of sexual behavior (courtship, mating and post-mating) of A. veniliae. The spiders were collected in transgenic soybean crops located in Chivilcoy (35º01' S - 60º06' W), Buenos Aires, Argentina, and reared under laboratory conditions. Based on observations of 20 couples (with virgin females), behavioral units of male and female in terms of postures and movements,including details on duration and frequency, were described at all stages of sexual activity (courtship, mating and post-mating). Courtship exhibited the greatest number and duration of behavioral units in both sexes. Male and female had a sequence of 16 and nine units, respectively, being the frequency of repetitions of the units significantly higher in the male. Mating was brief and males used a single palp to fill only one of the female spermathecae, after which the female became unreceptive. Mating had two behavioral units in the male and only one in the female. During post-mating males had three and females two behavioral units. The average duration of the whole sexual behavior was 541.90 ± 123.1 seconds for the male and 338.20 ± 74.1 seconds for the female. Alpaida veniliae females rarely accept a second mating with the same or another male (remating), indicating a strict monogamy. In 46% of observed mating, the female cannibalized the male after it. Females became unattractive after mating, since stop producing sex pheromones, causing a reduction of the male vibratory courtship. The high cost of courtship, including the risk of cannibalism, would reinforce the selectivity of males towards receptive virgin females.